Dose-effect of exercise intervention on heart rate variability of acclimatized young male lowlanders at 3,680 m - Su, Rui; Peng, Ping; Zhang, Wenrui; Huang, Jie; Fan, Jing; Zhang, Delong; He, Jiayuan; Ma, Hailin; Li, Hao (Frontiers in Physiology, 2024)
This study investigated whether exercise could improve the reduced HRV in an environment of high altitude. A total of 97 young, healthy male lowlanders living at 3,680 m for > 1 year were recruited.They were randomized into four groups, of which three performed-low-, moderate-, and highintensity (LI, MI, HI) aerobic exercise for four weeks, respectively. The remaining was the control group (CG) receiving no intervention. For HI, compared to other groups, heart rate (p = 0.002) was significantly decreased, while standard deviation of RR intervals (p < 0.001), SD2 of Poincaré plot (p = 0.046) and the number of successive RR interval pairs that differ by > 50ms divided by total number of RR (p = 0.032), were significantly increased after intervention. For MI, significantly increase of trigonometric interpolation in NN interval (p = 0.016) was observed after exercise. Further, a decrease in systolic blood pressure (SBP) after high-intensity exercise was found significantly associated with an increase in SD2 (r = -0.428, p = 0.042). These results indicated that there was a dose effect of different intensities of aerobic exercise on the HRV of acclimatized lowlanders. Moderate and highintensity aerobic exercise would change the status of the autonomic nervous system (ANS) and decrease the blood pressure of acclimatized lowlanders exposed to high altitude.